Antiplatelet and anticoagulant nonuse for acute myocardial infarction in the emergency department: An analysis from the National Hospital Ambulatory Medical Care Survey, 2002–2010. Issue 2 (2015) - Sethi, Ankur; Arora, Rohit R; Khosla, Sandeep
No abstract available